Omega-3 fatty acids promote neuroprotection, decreased apoptosis and reduced glial cell activation in the retina of a mouse model of OPA1-related autosomal dominant optic atrophy. (February 2022) - Kalogerou, Maria; Ioannou, Sotiris; Kolovos, Panagiotis; Prokopiou, Ekatherine; Potamiti, Louiza; Kyriacou, Kyriacos; Panagiotidis, Michail; Ioannou, Maria; Fella, Eleni; Worth, Elena Panayiotou; Georgiou, Tassos
Abstract: The purpose of this study was to evaluate the neuroprotective effects of omega-3 polyunsaturated fatty acid (ω3-PUFA) supplementation in a mouse model of OPA1-associated autosomal dominant optic atrophy (ADOA). The blood level of arachidonic acid (AA) and eicosapentaenoic acid (EPA) served to adjust the treatment dosage (AA/EPA = 1.0–1.5). Eight-month-old mice were allocated to four groups (n = 20/group): the ω3-PUFA-treated Opa1 enu/+, untreated Opa1 enu/+, ω3-PUFA-treated wild-type and untreated wild-type groups. Treated mice received the ω3-PUFAs, EPA and docosahexaenoic acid (DHA; 5:1 ratio) by daily gavage for 4 months based on the measured AA/EPA ratio. Blood, retina and optic nerve (ON) fatty acid levels were determined by gas chromatography, and the retina and ON were histologically examined. Western blotting and/or immunohistochemistry was performed to analyse retinal mediators involved in Opa1 -mutation-mediated apoptosis, inflammation and oxidative stress. Increased EPA and reduced AA levels were primarily observed predominantly in the blood and retinal tissues, and a similarly high EPA level tended to be observed in the ONs of ω3-PUFA-treated mice. Retinal ganglion cell and ON axonal densities were higher in both mouse strains upon ω3-PUFA treatment than in the corresponding untreated groups. Caspase-3 expression analysis showed fewer apoptotic retinal cells in both groups of treated mice. Decreases in inflammatory microglia and astrocytes activation and proapoptotic Bcl-2-associated X protein (Bax) expression were noted in the treated groups, with no difference in the antioxidant superoxide dismutase-2 expression. ω3-PUFA supplementation had neuroprotective effects on the retinas of Opa1 enu/+ and wild-type mice via blockade of microglia and astrocytes activation and suppression of Bax and caspase-3. Our findings indicated that inhibition of oxidative stress may not be involved in ω3-PUFA-mediated neuroprotection. These novel findings support the use of ω3-PUFAs as a beneficial therapy in the occurrence of ADOA, posing the basis for future clinical trials to confirm these observations. Highlights: Omega-3 fatty acid supplementation has neuroprotective effects on the retinas of a mouse model of OPA1-related autosomal dominant optic atrophy. Omega-3 fatty acids block the inflammatory activation of astrocytes and microglia in the retinas of Opa1 enu/+ mice. Omega-3 fatty acids suppress the proapoptotic Bcl-2-associated X protein and caspase-3 in the retinas of Opa1 enu/+ mice. These findings support the use of omega-3 polyunsaturated fatty acids as a therapy for autosomal dominant optic atrophy.